ANALYSIS OF COMMON STRATEGIES IN THE TRANSLATION OF HISTORICAL TEXTS - Abdullayeva Umida Abdumutal qizi (TADQIQOTLAR, 2026)
Abstract The translation of historical texts presents unique challenges due to the complexity of language, culture, and historical context. This article examines the most commonly used strategies in translating historical works, focusing on linguistic, cultural, and stylistic aspects. The study is based on a comparative analysis of selected historical texts and their translations into English, highlighting the ways translators address cultural realia, archaic terminology, and stylistic features. The findings indicate that strategies such as transliteration, adaptation, paraphrasing, and explanatory commentary are frequently employed to maintain the meaning, authenticity, and readability of the original text. The study concludes that successful translation of historical texts requires a balanced application of these strategies, combining linguistic accuracy with cultural and historical intelligibility.